Конституційні засади забезпечення прав людини в Україні - Лукіян, І. А.; Лукиян, И. А.; Lukijan, I. (My University, 2012)
In the article spectrum of rights and freedoms of man, reﬂ ected in modern Constitution of Ukraine, their humanism orientation is analyzed.
Лукіян І. А. Конституційні засади забезпечення прав людини в Україні / І. А. Лукіян // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2012. – Вип. 45. – С. 215-221.
Keywords: Конституція України; права і свободи людини за Конституцією України; гуманістична спрямованість прав і свобод людини; конституційне право України; Конституция Украины; права и свободы человека по Конституции Украины; гуманистическая направленность прав и свобод человека; конституционное право Украины; The Constitution of Ukraine; human rights and freedoms under the Constitution of Ukraine; humanistic orientation of human rights and freedoms; constitutional right of Ukraine